Communication Factors Affecting Tourist Adoption of Social Network Sites - Chien-Ta Bruce Ho (Sustainability, 2019)
Smart tourism technologies (STTs) are technological media that tourists apply in various stages of the tourism decision-making process. The purpose of this study was to explore how the communication elements of social network sites (SNSs), as a part of STTs, enhance tourists’ motivation and usage intention. A structural framework based on communication elements and the uses and gratification theory with regard to SNSs usage was developed and investigated. An online survey was employed for the data collection, and structural equation modeling was used in the hypotheses analysis. The findings indicated that Internet self-efficacy, information quality, and systems quality trigger the information-seeking motive while service quality and source credibility positively determine the relationship maintenance motive. The information-seeking motive, entertainment motive, relationship maintenance motive, and Internet self-efficacy positively influence the intention to use SNSs for trips. New findings were found in terms of the relationship between the motives. The information-seeking motive and relationship maintenance motive influence the entertainment motive. Moreover, the relationship maintenance motive influences the information-seeking motive.